WORKSHOP KAJIAN PENTINGNYA KEBERADAAN HERITAGE UNTUK MENUMBUHKAN KEPEDULIAN PENDIDIKAN BAGI GURU BIOLOGI KABUPATEN TANGGAMUS - Meriza, Nadya; Surbakti, Arwin; Pramudiyanti; Wisnu Juli Wiono (FT Universitas Lampung, 2023)
The results of the study on biodiversity of students in class X high school in a heritage site contained some biodiversity material that had not maximized the results regarding the content of heritage as determined by UNESCO, namely the Bukit Barisan Selatan National Park (TNBBS) in the Tanggamus district. The results of this study have not been linked to learning in schools, especially in schools located around heritage. The MGMP in biology accommodates learning problems including real-world problems in the surrounding environment. Biology MGMP activities in Tanggamus Regency are still not touched by the issue of heritage biodiversity in the learning process. other than that it has not been seen working with the Ministry of Forestry. The Ministry of Forestry is a very important partner regarding biodiversity material, which this material must be studied according to the demands of the school curriculum. The MGMP workshop in the field of biology partnered with the Ministry of Forestry and the University of Lampung Research Team to produce products in the form of Learning Implementation Plans, LKPD, and learning media. The product contains topics related to biodiversity which were developed through FGDs in Tanggamus Regency at heritage sites. It is hoped that this activity will enable teachers to convey reliable biodiversity knowledge to change students' paradigms regarding the importance of developing world heritage conservation.